PENGARUH KOMITMEN ORGANISASI, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI SAE PUJON KABUPATEN MALANG - M. Agung Jaya Satria; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT         Environment as independent variable, employee performance as dependent variable. Samples used are employees of the Koperasi SAE Pujon of Malang Regency as many as 57 respondents with using survey method. Data collection method by using questionnaire (questionnaire). The analysis used with including instrument test, classical assumption test, normality test, multiple regression linear test, hypothesis test and coefficient of determination test using multiple linear regression analysis with SPSS 14.0 Version for windows software                The result of the research shows, that the organization comitment, has significant influence to the performance of employees of the Koperasi SAE Pujon of Malang Regency, the motivation has significant influence to the performance of employees of the Koperasi SAE Pujon of Malang Regency and the work environment has a significant effect on the performance of the employees of the Koperasi SAE Pujon of Malang Regency. The organization comitment,  motivation and work environment together affect the performance of the employees of Koperasi SAE Pujon of Malang Regency. Keywords     : organization comitmen, motivation, work environment, employee performance